Ourselves among others : - Verburg, Carol J. (Bedford Books of Saint Martin's Press, 1988)
This adventurous thematic reader exposes students to stimulating writing from the United States and abroad in the context of 6 familiar themes, giving them a critical, cross-cultural perspective on the United States — essential in today's global society